2012
DOI: 10.1080/13803395.2011.648175
|View full text |Cite
|
Sign up to set email alerts
|

Influence of poor effort on neuropsychological test performance in U.S. military personnel following mild traumatic brain injury

Abstract: The purpose of this study was to examine the influence of poor effort on neuropsychological test performance in military personnel following mild traumatic brain injury (MTBI). Participants were 143 U.S. service members who sustained a TBI, divided into three groups based on injury severity and performance on the Word Memory Test and four embedded markers of poor effort: MTBI-pass (n = 87), MTBI-fail (n = 21), and STBI-pass (n = 35; where STBI denotes severe TBI). Patients were evaluated at the Walter Reed Arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 57 publications
6
33
0
1
Order By: Relevance
“…Simulators produced the highest mean validity scores on NIM. Their findings are consistent with previous research in which high scores on NIM have been associated with poor effort on PVTs or compensation-seeking populations (see Lange, Pancholi, Bhagwat, Anderson-Barnes, & French, 2012). For instance, higher NIM scores were observed for compensation-seeking patients with mild TBIs than for patients who were not compensation seeking but also had mild TBIs (Whiteside, Galbreath, Brown, & Turnbull, 2012).…”
Section: Pai In Psychological Injury and Related Evaluationssupporting
confidence: 92%
“…Simulators produced the highest mean validity scores on NIM. Their findings are consistent with previous research in which high scores on NIM have been associated with poor effort on PVTs or compensation-seeking populations (see Lange, Pancholi, Bhagwat, Anderson-Barnes, & French, 2012). For instance, higher NIM scores were observed for compensation-seeking patients with mild TBIs than for patients who were not compensation seeking but also had mild TBIs (Whiteside, Galbreath, Brown, & Turnbull, 2012).…”
Section: Pai In Psychological Injury and Related Evaluationssupporting
confidence: 92%
“…Study results also demonstrate that despite the use of an effort measure with limited sensitivity, the base rate of PVT failure in a military sample was still notable. Taken together, these results support previous findings [37][38]54] highlighting the importance of PVTs in an Active Duty military population referred for mTBI evaluation. ).…”
Section: Discussionsupporting
confidence: 82%
“…Also, similar to the findings of Gallun et al, the performance of the participants in the current study was The finding that performance is poor on some but not all measures suggests that participants exhibit taskspecific deficits rather than a global functional deficit. It has, however, been noted in both civilian and Veteran populations that poor effort and symptom exaggeration are common following TBI [52][53] and that poor effort can account for more than 50 percent of the variance on cognitive performance [54]. Indeed, it has been suggested that Veterans who sustained TBI that report postconcussive symptoms differ from those who do not report postconcussive symptoms on, among other things, degree of possible symptom exaggeration, poor effort, depression, and traumatic stress, while postconcussive disorder rarely occurred in the absence of these symptoms [55].…”
Section: Discussionmentioning
confidence: 99%